Child abuse: methodological support for a descriptive survey and for monitoring in a specialised team which takes charge of abused children. (1st March 2011) - Senterre, C; Vanthournout, B; Rebuffat, E; Gerard, M; Dramaix, M
Abstract : Child abuse is a well-known problem but still poorly documented in Belgium. Since 2005, SOS enfants that takes care of abused children tries to analyse the evolution of its populations. The team decided to create a data collector form for hospitalised children This tool included data on children and parental characteristics, criteria for hospitalisation, history and types of abuse and clinical diagnosis. Since 2008, the Department of Biostatistics supports the team for methodological and analytical process. A data entry program was locally implemented (with Epi 6) to improve the potential for 'routine monitoring' tool. The purpose of this paper is to present the major results of the analysis of the data collected between 2005 and 2008 (n=350 children). The abuse is confirmed in about 75% of the hospitalisations and in one in five cases, it was multiple abuses (often physical and sexual). Family histories of these children were also very complicated: history of abuse, reconstituted family, socio-economic difficulties, etc. In conclusion, systematic data collection and analysis have permitted a better knowledge of the populations characteristics and conducted the team to venture clinical hypotheses about history of abuse.